Mothers, fathers, and guardians in education during the pandemic. The rural-urban dichotomy in Ecuador - Juan Cárdenas-Tapia; Fernando Pesántez-Avilés; Angel Torres-Toukoumidis (Íconos, 2022)
This article analyzes the involvement of mothers, fathers, and legal guardians in the active learning of children in primary and secondary schools in a particular scenario: online learning during the COVID-19 pandemic in Ecuador. For this purpose, a 45-question survey was applied to a sample of 6,206 people, segmented according to their geographic areas. In the rural area, the degree of involvement in virtual teaching-learning processes is reflected, in particular, in the establishment of sleep schedules and the acknowledgement by student of criticisms of their activities. For the urban area, children’s anger management and the recognition of their strengths in subject matters are evident. In terms of strategies, in rural areas, parents put more pressure on students to carry out school activities, whereas in urban areas, parents talk more with their children when they lose control, paying more attention to their emotions and needs. Thus, the differentiation is summarized in the following expression: in rural areas, mothers, fathers, and guardians focus on discipline, while in urban areas they are oriented towards the academic and emotional spectrum.